Clinical study of benign lesions of larynx - M. Muniraju; Vidya H. (International Journal of Medical Research and Review, 2017)
Aim of Study: To analyze over a period of 2 years, the demographics such as age, sex, distribution, occupation, the site of involvement, symptomatology and prognosis of the most frequent benign lesions of larynx.Materials and Methods: 50 patients presenting with hoarseness of voice and diagnosed with benign lesion of larynx in ENT OPD of Dr. B.R.Ambedkar Medical College and Hospital were included in the study after taking their consent and the study was carried out for a period of 2 years between October 2013 to September 2015.Results: In this study, it was noted that males were predominantly involved, maximum incidence between 31-40 years. Business men among males and housewives among females were commonly involved. Bilateral vocal cord nodule was the most common benign lesion of larynx, others included vocal cord polyp (both unilateral and bilateral) and Reinke’s edema. Most important predisposing factor was being vocal abuse in all the cases. Treatment given included speech therapy, medical management and MLS according to the diagnosis and patients were followed up for six months. 41.18% of patients with bilateral vocal cord nodule, 50% of patients with bilateral vocal cord polyp, 50% of patients with right vocal cord nodule, 75% of patients with left vocal cord polyp, 42.86% of patients with right vocal cord polyp and 100% of patient’s with Reinke’s edema were normal at follow up.Conclusion: It was observed that vocal abuse was the most common predisposing factor for benign lesions of larynx and a multi modality treatment is necessary including medical, surgical and speech therapy to prevent recurrence.